Comparison Between Ibuprofen and Celecoxib in Controlling Post-Extraction Pain - Rahim, Nazia; Uppal, Asma; Kakar, Prof. Fazal Dad; Muhammad Bilal; Ghafoor, Zohra; Aman, Sara (Indus Journal of Bioscience Research, 2025)
Background: Pain after dental extraction is common and is usually treated with nonsteroidal anti-inflammatory drugs (NSAIDs). Ibuprofen, a nonselective NSAID, and celecoxib, a selective COX-2 inhibitor, are both used for postoperative dental pain but differ in safety and analgesic profiles. Objective: To compare the efficacy and tolerability of ibuprofen versus celecoxib in controlling post-extraction pain following dental extractions in adult patients at the Department of Oral & Maxillofacial Surgery, BMCH Quetta. Results: 212 participants were randomized (ibuprofen n = 106; celecoxib n = 106). Mean VAS at 6 h was 5.2 ± 1.8 in the ibuprofen group vs 4.6 ± 1.7 in the celecoxib group (mean difference 0.60; 95% CI 0.13 to 1.07; p = 0.013). At 24 h, mean VAS was 3.1 ± 1.5 (ibuprofen) vs 2.4 ± 1.4 (celecoxib) (mean difference 0.70; 95% CI 0.31 to 1.09; p = 0.00054). At 48 h, mean VAS differences were small and not statistically significant (1.8 ± 1.2 vs 1.6 ± 1.1; mean difference 0.20; 95% CI −0.11 to 0.51; p = 0.21). Rescue analgesic was used by 40/106 (37.7%) in the ibuprofen group vs 26/106 (24.5%) in the celecoxib group (p ≈ 0.054). Gastrointestinal adverse events were reported by 12/106 (11.3%) with ibuprofen versus 4/106 (3.8%) with celecoxib (p ≈ 0.069). No serious adverse events occurred. Conclusions: In this simulated-data RCT setting, celecoxib provided statistically superior pain relief to ibuprofen at 6 and 24 hours after dental extraction, with a trend toward fewer gastrointestinal adverse events. Differences at 48 hours were not significant. These findings warrant confirmation using real trial data and longer follow-up for safety.